The influence of product quality and price on consumer satisfaction at the 3R Tofu Factory, Majalengka - Sari, Gita Kartika; Kamaludin, Ahmad; Andita, Vina; Nurlaeliah, Leli (Institute of Accounting Research and Novation (IARN), 2024)
The purpose of this research was to determine the effect of product quality and price on customer satisfaction at Pabrik Tahu 3R, Majalengka.The data collection method used in this study was a questionnaire.The population in this study are consumers who purchase products at Pabrik Tahu Tahu 3R,Majalengka.Sampling was calculated using the Lameshow formula and obtained as many as 96 respondents using the Accidental sampling technique.The analysis used in this study includes validity test,reliability test,multiple linear regression analysis, correlation coefficient analysis,determination coefficient analysis,and hypothesis testing T-test and F-test with SPSS V26.0 data processing.The results showed that product quality and price proved to have a positive and significant effect on customer satisfaction.This is evidenced by the analysis of the regression equation,Y=4.590+0.166X1+0.438X2.From this equation,it can be concluded that with a constant value of 4.590 and a positive value,it means that if the value of the product quality and price variable is zero,then the customer satisfaction will experience an increase of 4.590.The value of the correlation coefficient(r)=0.710,which means that the relationship between product quality and price with customer satisfaction is at a fairly strong level of relationship.The results of the test for the coefficient of determination show that the effect of price and product quality on customer satisfaction is 50,4%,while the remaining 49,6% is influenced other variables not used in this study.Meanwhile, the value of Fcount>Ftable,namely(47,204>3.094) product quality and price together influence customer satisfaction.